In Silico Evaluation of Antioxidant Potential of Adenostemma lavenia Leaf Compounds Against IL-6 in Pulmonary Sepsis - Polem, Wardah Sawitri; Ilyas, Syafruddin; Tanjung, Masitta (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to evaluate the antioxidant potential of bioactive compounds from Adenostemma lavenia in targeting interleukin-6 (IL-6) associated with pulmonary sepsis. Phytochemicals from Adenostemma lavenia leaves were identified using GC-MS, and ten bioactive compounds with potential antioxidant activity were selected. These compounds underwent further in silico evaluation, including drug-likeness screening, biological activity prediction, pharmacokinetic and toxicity analysis, and molecular docking against interleukin-6 (PDB ID: 8J6F). Among them, stigmasterol showed the highest docking score of –8.1 kcal/mol and a PASS prediction probability (Pa) of 0.867 for antioxidant activity. Half of them fully complied with drug-likeness criteria. Among these, D-Allose, 2,4-Di-tert-butylphenol, and Phytol demonstrated the highest predicted antioxidant activity. Toxicity evaluations revealed a generally safe profile, with minimal nephrotoxicity in two compounds. Notably, Phytol exhibited the closest similarity in binding residues to the native ligand of IL-6, suggesting a strong binding orientation and promising therapeutic value. The in silico findings highlight Phytol and other antioxidant-rich phytoconstituents of A. lavenia as promising agents targeting IL-6, supporting their potential use as adjunct therapies for oxidative stress-related conditions such as pulmonary sepsis. These results contribute to the scientific understanding of natural antioxidants in inflammation control and warrant further validation through in vitro and in vivo studies.